Keragaman Mikroflora, Mikrofauna, Kandungan C-organik, dan Total N Tanah Sawah Akibat Aplikasi Azolla dan Pupuk Hayati - Mieke Rochimi Setiawati; Pujawati Suryatmana; Tualar Simarmata (Fakultas Pertanian Universitas Padjadjaran, 2020)
This study was conducted to determine the effect of Azolla pinnata and biofertilizers (Azotobacter and Phosphate Solubilizing Bacteria) on the total microflora, microfauna, organic C, N-total soil, and C/N ratio of soil in lowland rice. The study was carried out in the SPLPP experimental field (Agricultural Research and Development Research Studio) of the Faculty of Agriculture, Padjadjaran University, Jelekong Village, Ciparay, Bandung Regency, West Java, with an altitude of 628 meters above the sea level. The experimental design used was factorial randomized block design consisted of two factors and repeated four times. The first factor was the provision of Azolla with two levels: without Azolla and 3 tons ha-1 of Azolla pinnata. The second factor was the provision of biofertilizer with three levels, without biofertilizer, 5 L ha-1 biofertilizer, and 10 L ha-1 biofertilizer. The results showed that there was an interaction between A. pinnata with biofertilizer on the increase in the total bacterial population. Total fungus, microfauna (nematodes), and soils N-total content did not increase with the addition of Azolla or biofertilizers. Independently A. pinnata increased soil C-organic matter while biofertilizer 10 L ha-1 increased the total population of actinomycetes.